Seeking the significance of music education [ essays and reflections - Reimer, Bennett; MENC, the National Association for Music Education (US) (Lanham, Md : Rowman & Littlefield Education, 2009)
"Noted music educator Bennett Reimer has selected 24 of his previously published articles from a variety of professional journals spanning the past 50 years. During that time, he's tackled generating core values for the field of music education; the core in larger societal and educational contexts; what to teach and how to teach it effectively; how we need to educate our teachers; the role of research in our profession; and how to improve our future status."--Provided by publisher
1. Our values as a school subject. Generating core values ; Core values in larger contexts -- 2. Achieving our values. What and how to teach ; Educating our teachers ; The role of research -- 3. Preserving and enhancing our viability. Our values in service of our future
"Published in partnership with MENC, The National Association for Music Education"
Description based on print version record
Includes bibliographical references
Keywords: Music -- Instruction and study -- Philosophy